Hepatoprotective Effects of β-Caryophyllene and Full-Spectrum Cannabis Extract Against Paracetamol-Induced Liver Injury in Mice - Abdelmaaboud, Ragaa; A. Kassim, Ensaf; M. Abdulla, Ehab; S. Ahmed, Amira; S. Abd-Elgwad, Radwa (Libyan Journal of Medical and Applied Sciences, 2026)
Background: Paracetamol overdose is a leading cause of acute liver injury. N-acetylcysteine (NAC) is the standard treatment but has limitations, including adverse reactions. Cannabis-derived compounds, particularly β-caryophyllene (BCP), have demonstrated anti-inflammatory and antioxidant effects through CB2 receptor activation. Objectives: This study aimed to (i) determine the concentrations of cannabinoid constituents in commercially available Cannabis sativa samples and (ii) evaluate the efficacy of BCP and full-spectrum cannabis extract in mitigating paracetamol-induced hepatotoxicity in mice. Methods: Four cannabis samples were analysed by GC-MS. Forty-two male albino mice were divided into seven groups, including negative and positive controls, paracetamol toxicity, BCP and cannabis treatment groups, and combination treatment groups. Serum ALT and AST levels were measured, and liver tissues were assessed histologically using hematoxylin–eosin staining. Statistical analysis was performed using t-tests and ANOVA with LSD post hoc tests. Results: GC–MS analysis identified distinct cannabinoid profiles among the investigated cannabis samples, indicating differences in their phytochemical composition. In vivo, administration of β-caryophyllene (BCP) and full-spectrum cannabis extract significantly attenuated paracetamol-induced hepatotoxicity, as demonstrated by reduced serum ALT and AST levels compared with the untreated paracetamol group (p ≤ 0.05). Histological assessment corroborated these findings, revealing improved hepatic architecture in both treated groups. Importantly, the BCP-treated group exhibited a more pronounced hepatoprotective effect, characterised by greater normalisation of liver enzyme levels and enhanced preservation of liver histoarchitecture relative to the full-spectrum extract. Conclusion: Both β-caryophyllene and full-spectrum cannabis extract exhibit significant hepatoprotective properties against paracetamol-induced liver injury. β-caryophyllene, however, demonstrated superior efficacy across biochemical and histopathological parameters, underscoring its potential as a therapeutic agent. These findings support further experimental and clinical investigations to explore its mechanism of action and potential applications in liver disease management.